2005
DOI: 10.1007/s00394-005-0568-5
|View full text |Cite
|
Sign up to set email alerts
|

The bioavailability of polyphenols is highly governed by the capacity of the intestine and of the liver to secrete conjugated metabolites

Abstract: Genistein and hesperetin appeared less available than FA for peripheral tissues because of a high intestinal and biliary secretion of their conjugates. Moreover, data suggest that a high polyphenol intake may improve their bioavailability due to saturation of the intestinal secretion of conjugates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
88
0
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(100 citation statements)
references
References 36 publications
6
88
0
2
Order By: Relevance
“…(52) A further explanation may be that those with high intakes of hesperidin may have a greater ability to secrete the metabolites required for its absorption, thus increasing bioavailability. (36) This cross-sectional study of over 3000 women has shown associations between greater intakes of dietary flavonoids and improved bone health, although causality cannot be inferred owing to the study design. To conclude, there are associations between flavonoid intakes and healthy bones, but these associations are not strong and should be considered only as indicators.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…(52) A further explanation may be that those with high intakes of hesperidin may have a greater ability to secrete the metabolites required for its absorption, thus increasing bioavailability. (36) This cross-sectional study of over 3000 women has shown associations between greater intakes of dietary flavonoids and improved bone health, although causality cannot be inferred owing to the study design. To conclude, there are associations between flavonoid intakes and healthy bones, but these associations are not strong and should be considered only as indicators.…”
Section: Discussionmentioning
confidence: 94%
“…The validity study did not use biomarkers because correlations between these and dietary records of flavonoid intakes are not good (r ¼ 0.35) (33) owing to their bioavailability and metabolism in the gut. (34)(35)(36) Limitations of this study include those associated with using an FFQ because FFQs are known to overestimate the true overall frequency of consumption of fruit and vegetables. (37,38) There are issues that affect the flavonoid content of foods, namely, analytical and environmental factors, processing, storage, and species differences, and these cannot be detected using a FFQ because it is a crude measure of diet.…”
Section: Discussionmentioning
confidence: 99%
“…Only 0.5-0.8% is found in feces of mice (Zhao et al, 2003). After absorption, about 50% of FA reaches the liver, and the remainder is distributed in the bloodstream, gastric mucosa and peripheral tissues (Adam et al, 2002;Zhao et al, 2004;Silberberg et al, 2006). Chang et al (1993) administered pure FA in Wistar rats and found that the free acid did not enter the enterohepatic circulation.…”
Section: Preclinical Pharmacokineticmentioning
confidence: 99%
“…Direct interactions between PCs and other food components, such as bonds with proteins and polysaccharides, and direct effects, such as that of pH, can interfere with the PC absorption by the gut (Silberberg et al, 2006). In relating the results obtained in this study to physiological parameters and the PC bioavailability, we conclude, based on the low levels of adsorption observed, that adsorption of catechin, caffeic acid and ferulic acid by the DFs cellulose and xylan would not compromise their absorption by the intestinal epithelial cells, where most of the phenols are known to be absorbed, especially at a pH close to 7.0 (Dliveira & Bastos, 2011).…”
Section: Physiological Considerationsmentioning
confidence: 99%
“…These compounds include a wide variety of molecules, like phenolic acids, the simplest ones, consisting in a C6-C1 or C6-C3 structure, the flavonoids, which are the most abundant and presenting a C6-C3-C6 structure, and the stilbenes with their C6-C2-C6 structure. The consumption of certain foods may alter the bioavailability of PCs through their direct interaction with others food components, such as proteins and polysaccharides (Manach et al, 2004;Silberberg et al, 2006;D' Archivio et al, 2010). Due to the individual benefits of PCs and DFs, the food and pharmaceutical industries have shown great interest in these bioactive compounds.…”
Section: Introductionmentioning
confidence: 99%